1996
DOI: 10.1016/s0006-3495(96)79592-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the sources of protein-ligand affinity: 1-sulfonato-8-(1')anilinonaphthalene binding to intestinal fatty acid binding protein

Abstract: 1-Sulfonato-8-(1')anilinonaphthalene (1,8-ANS) was employed as a fluorescent probe of the fatty acid binding site of recombinant rat intestinal fatty acid binding protein (1-FABP). The enhancement of fluorescence upon binding allowed direct determination of binding affinity by fluorescence titration experiments, and measurement of the effects on that affinity of temperature, pH, and ionic strength. Solvent isotope effects were also determined. These data were compared to results from isothermal titration calor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
111
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(126 citation statements)
references
References 44 publications
15
111
0
Order By: Relevance
“…The binding of ANS was well described by the single binding site equation. The derived dissociation constant (2.9 M) is comparable with K d values reported previously for the unmodified rat protein (6.9 M, Kirk et al, 1996;3.6 -7.4 M, Velkov et al, 2005). Scatchard analysis indicated that each molecule of IFABP bound one molecule of ANS.…”
Section: Ifabp Expression and Ans And Arachidonic Acid Bindingsupporting
confidence: 90%
“…The binding of ANS was well described by the single binding site equation. The derived dissociation constant (2.9 M) is comparable with K d values reported previously for the unmodified rat protein (6.9 M, Kirk et al, 1996;3.6 -7.4 M, Velkov et al, 2005). Scatchard analysis indicated that each molecule of IFABP bound one molecule of ANS.…”
Section: Ifabp Expression and Ans And Arachidonic Acid Bindingsupporting
confidence: 90%
“…In principle, it is possible that it binds to the DNA binding site and at the central cavity of the barrel, or some other accessible non-polar site. The presence of more than one site is supported by the biphasic changes in the wavelength maximum, indicative of sites of different polarity (28). To complement our conformational analysis, we used the extreme sensitivity of bis-ANS to investigate conformational changes caused by ionic strength, phosphate, DNA, and heparin on the E2 domain.…”
Section: Discussionmentioning
confidence: 99%
“…ANS is a hydrophobic fluorescent molecular probe that has been used for examining the non-polar character of proteins and membranes [23][24][25]. ANS binding is used to study changes in exposed hydrophobicity in Aβ 42 upon incubation in the presence and absence of crocin.…”
Section: Ans-binding Studymentioning
confidence: 99%